Strategies for Competence Development in Dynamic Business Landscapes - Marillo, Christine; Freeman, Barbara; Espanha, Almeida; Watson, Jeffrey; Viphindrat, Barrack (First Ciera Publisher, 2024)
In today's rapidly evolving business landscape, organizations face unprecedented challenges in sustaining competitiveness due to technological disruptions, globalization, and unpredictable market dynamics. To thrive amidst this turbulence, the cultivation of relevant competences has become a strategic imperative. This study explores competence development strategies tailored for navigating dynamic business landscapes. Through a mixed-methods approach, including qualitative interviews, focus groups, and quantitative surveys, key practices, challenges, and opportunities in competence development are examined. Findings reveal a variety of strategies, including continuous learning initiatives, agile talent management, and innovation ecosystems, employed by organizations to enhance competences. Additionally, the study highlights the importance of organizational resilience, change management, and ethical leadership in fostering adaptability and innovation. Recommendations for organizational leaders, practitioners, and scholars include embracing digital transformation, fostering learning cultures, addressing ethical challenges, investing in talent management, and promoting lifelong learning. While providing valuable insights, the study acknowledges limitations such as sample representativeness and reliance on self-reported data, suggesting avenues for future research. Overall, this study contributes to advancing understanding of competence development in dynamic business landscapes, offering actionable insights for organizational success amidst uncertainty and change.